مستوى معرفة معلمي الأطفال المعاقين عقليا بمبادئ وأساليب تعديل السلوك وعلاقتها ببعض المتغيرات - عبدالعزيز، عمر فواذ (جامعة المنصورة - كلية التربية النوعية, 2012)
هدفت هذه الدراسة التعرف إلى مستوى معرفة معلمي الأطفال المعاقين عقليا بمبادئ وأساليب تعديل السلوك وعلاقتها بالجنس والتخصص العلمي. تكونت عينة الدراسة المسحية من (68) معلم ومعلمة من العاملين بمعهدي التربية الفكرية للبنين والبنات في مدينة جدة، بلغ عدد المعلمين (39) وعدد المعلمات (29) وتم بناء اختبار معرفة المعلمين بمبادئ وأساليب تعديل السلوك من قبل الباحث وتم التحقق من صدقه وثباته. واشتمل اختبار معرفة المعلمين بمبادئ وأساليب تعديل السلوك على ثلاثة مستويات هي: -الأول: المبادئ العامة الأساسية في تعديل السلوك. -الثاني: أساليب تقوية السلوك المرغوب. -الثالث: أساليب التقليل من السلوك غير المرغوب. وللإجابة عن أسئلة الدراسة تم استخدام تحليل التباين للقيم المتكررة. وأشارت نتائج الدراسة إلى ما يلي: 1-إن مستوى معرفة معلمي الأطفال المعاقين عقليا بمبادئ وأساليب تعديل السلوك بشكل عام كانت متوسطة وأن أعلى مستوى معرفة كانت في أساليب تقوية السلوك المرغوب. 2-توجد فروق ذات دلالة إحصائية عند مستوى ( 0.05) في مستوى معرفة معلمي الأطفال المعاقين عقليا بمبادئ وأساليب تعديل السلوك تعزى لمتغير الجنس ولصالح الإناث مقارنة بالمعلمين الذكور. 3-توجد فروق ذات دلالة إحصائية عند مستوى ) 0.05) في مستوى معرفة معلمي الأطفال المعاقين عقليا بمبادئ وأساليب تعديل السلوك تعزى لمتغير التخصص العلمي ولصالح المعلمين الذين يحملون تخصصا علميا تربية خاصة (إعاقة عقلية) مقارنة بالمعلمين من ذوي التخصصات الأخرى.
This study aimed to identify the knowledge level of Teachers of Children with mental retarded in Behavior modification. The sample of survey study included (68) male and female teachers working in in both intellectual education in statutes for boys and girls in jeddah. The sample study will be (39) male and (29) female to achieve these study objectives, the researcher developed a test consisting of multiple - choice question, with satisfactory content validity and reliability .This test covered three levels: I: General Principles of behavior modification. II: methods to strengthen the desired behavior. Ill: Methods of weakening the unwanted behavior. To answer the question of the study, the difference analysis of recurring values (MANCOVA) and repeated measures were used. Finding of The study indicated the following: 1- The knowledge level of Teachers of students with mental retarded of Behavior modification, in general, was mediocre, and the highest knowledge level was in methods of strengthening the desired behavior. 2- There are differences with statistical indication at ( P=0,05) in the knowledge level of Teachers of students with mentally retarded of Behavior modification methods attributed to sex variable and to the advantage of female, compared to male teachers . 3- There are differences with statistical indication at (P=0, 05) in the knowledge level of Teachers of students with mentally retarded of Behavior modification attributed to qualification to the advantage of teachers that have qualification (special education - major: mentally retarded).
Keywords: معلمو التربية الخاصة -- علم النفس التربوي -- الإعاقة العقلية